2021
DOI: 10.1021/acs.inorgchem.1c02487
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Ligand Cooperation in Cp*Ir-Pyridylpyrrole Complexes: Rational Design and Catalytic Activity in Formic Acid Dehydrogenation and CO2 Hydrogenation under Ambient Conditions

Abstract: Interconversion between CO 2 + H 2 and FA/formate is the most promising strategy for the fixation of carbon dioxide and reversible hydrogen storage; however, FA dehydrogenation and CO 2 hydrogenation are usually studied separately using different catalysts for each reaction. This report describes of the catalysis of [Cp*Ir(N∧N)(X)] n+ (Cp* = 1,2,3,4,5-pentamethylcyclopentadienyl; X = Cl, n = 0; X = H 2 O, n = 1) bearing a proton-responsive N∧N pyridylpyrrole ligand for both reactions. Complex 2-H 2 O catalyzes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 57 publications
4
16
0
Order By: Relevance
“…Consequently, the formation of the iridium hydride species (Ir–H) from the iridium-formato intermediate (Ir–OCHO) via β-hydride elimination and CO 2 release, rather than the H 2 elimination by the reaction of the Ir–H intermediate with proton (H + or H 2 O) would govern the rate of the reaction of the present Ir - 1 -catalyzed reaction. The same trend has been reported by the groups of Himeda and Xiao, where generation of Ir–H was the rate-limiting step for the dehydrogenation of formic acid. ,, …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Consequently, the formation of the iridium hydride species (Ir–H) from the iridium-formato intermediate (Ir–OCHO) via β-hydride elimination and CO 2 release, rather than the H 2 elimination by the reaction of the Ir–H intermediate with proton (H + or H 2 O) would govern the rate of the reaction of the present Ir - 1 -catalyzed reaction. The same trend has been reported by the groups of Himeda and Xiao, where generation of Ir–H was the rate-limiting step for the dehydrogenation of formic acid. ,, …”
Section: Resultssupporting
confidence: 84%
“…With these couples, not only an effective carbon-neutral H 2 -based fuel system but also the carbon capture and utilization (CCU) protocol can be implemented at a time. Obviously, to materialize such systems, among other factors, developing efficient catalysts for bidirectional CO 2 (or HCO 3 – ) hydrogenation and HCO 2 H (or HCO 2 – ) dehydrogenation is equally important. In the domain of homogeneous transition metal-based catalysis, although a great advancement has already been achieved for the individual hydrogenation and dehydrogenation reactions with two different catalysts, there are only a limited number of reports in the literature describing both the processes using a single catalyst. Among these, some catalysts are relatively more active in hydrogenation than dehydrogenation, , while some others are the opposite. ,,, Single bidirectional transition metal catalysts, which are highly efficient in both hydrogenation and dehydrogenation, are so far designed with phosphine-based (PNP pincer) or N , N -donor-based ligands (Figure B).…”
Section: Introductionmentioning
confidence: 99%
“…This induction period might be due to the possible formation of poorly active (or inactive), out-of-cycle, dinuclear species. 101 As discussed above, most of the Ir sites in Ir_PicaSi_SiO 2 are well separated (≈1 Ir every 10 nm 2 ), making the associative process unlikely. After 6 h, the activity of Ir_PicaSi_SiO 2 decreased to 231 h –1 , whereas that of 3 decreased down to 418 h –1 .…”
Section: Results and Discussionmentioning
confidence: 94%
“…30 min, which is absent in that of Ir_PicaSi_SiO 2 (Figure b). This induction period might be due to the possible formation of poorly active (or inactive), out-of-cycle, dinuclear species . As discussed above, most of the Ir sites in Ir_PicaSi_SiO 2 are well separated (≈1 Ir every 10 nm 2 ), making the associative process unlikely.…”
Section: Results and Discussionmentioning
confidence: 99%
“…32,33 Hydrogen generated from aqueous FA could avoid the aforementioned problems. Those iridium-based complexes were found to be particularly efficient in this field, 34,35 including [Cp*Ir(DHBP) (H 2 O)] (DHBP = 4,4′-dihydroxy-2,2′-bipyridine; TOF = 14 000 h −1 ), 36 N^C cyclometallated iridium(III) complexes based on 2-aryl imidazoline ligands (TOF = 147 000 h −1 ), 37 [Cp*Ir(2,2′-bi-2-imidazoline)Cl]Cl (TOF = 487 500 h −1 ), 38 Ir complexes with picolinamide-based ligands [39][40][41] and pyridylidene-amine ligands containing a chelating phenolate (TOF = 280 000 h −1 ), 42 cis-mer-[IrH 2 Cl(mtppms) 3 ] (mtppms = monosulfonated triphenylphosphine) (TOF = 298 000 h −1 ), 43 Ir complexes with diphenylethylenediamine derivatives (TOF = 11 000 h −1 ) 44 etc. Through the investigation of the structureactivity relationship of these catalysts, researchers found that electron-donating moieties on the ligands, 36,[45][46][47][48] utilization of N-heterocyclic rings with higher electron density 49,50 and pendent-group effects [51][52][53] could improve the reaction rate for FADH.…”
Section: Introductionmentioning
confidence: 99%